Critical Evaluation of Avicennian Cardiac Drugs in the Contemporary Research - Rahman, Syed Ziaur; Mubashir, SM; Jamal, SH Zahid (International Journal of Human and Health Sciences (IJHHS), 2020)
Lots of clinical and experimental research work had been done to screen the cardiac drugs mentioned by Ibn Sina (980-1037) for their efficacy and safety. Similarly, annotated bibliography of his other works such as major philosophical work (Kitab Shifâ), major medical work (Qanun fil Tibb), minor collective works on logics, poetry, physics, psychology, chemistry-magic, mathematics, music, astronomy, metaphysics, Quranic exegesis, mysticism, ethics, politics, prophecy, etc. and critical editions in almost all languages had been prepared and arranged, which includes publications and references in all major languages. But, to the best of our knowledge, no critical descriptive study has ever been done so far to evaluate the scientific report on all 63 cardiac drugs mentioned in his another famous work, Kitab-al Advia Al Qalbia. There is a need to comment on these drugs on the basis of clinical and experimental study regarding the utility of Ibn Sina’s cardiac drugs. Some of these drugs could be found safe without any reported adverse reactions. Such drugs with safe profile need to be further explored, to select promising and accessible drugs. If toxic effects are reported, then the flagging of such drugs and its present position in clinical utilization should be delineated. The present paper deals and discusses the cardiac drugs described by Ibn Sina in the contemporary research after extensive literature review and meta-analysis. The present work, therefore, provides a useful resource to enable a thorough assessment of the profile of Ibn Sina’s Cardiac drugs that have cardioprotective activity. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 257-266